Haemodialysis vascular access function in dialysis patients at the Kenyatta National Hospital - Ndinya, Florentius O; Kayima, Joshua K; Magabe, Peter C; McLigeyo, Seth O; Were, Antony J; Odinya, George O (African Journal of Nephrology, 2019)
Background: The number of patients requiring renal replacement therapy (RRT) worldwide has been on the rise. Vascular access is the lifeline for these patients when haemodialysis (HD) is the treatment of choice. Access-related morbidity is a leading cause of hospitalization so that the function and patency of access are essential for the optimal management of patients. There is a need to recognize when a vascular access is dysfunctional because intervention must maintain function as well as preserve future vascular access sites. Methods: This was a cross-sectional study that evaluated the haemodialysis vascular access function in patients undergoing chronic haemodialysis at the Kenyatta National Hospital, Nairobi, Kenya. Peak access blood flow rates, urea reduction ratio (URR) and Kt/V were analysed in 150 patients. Results: The temporary (non-tunnelled) central venous dialysis catheters had poor function, with only 48% achieving a mean blood flow rate > 300 mL/min. The comparable rate for arteriovenous fistulae (AVF) was 88% and for tunnelled dialysis catheters 82%. One-quarter of the patients had a URR < 65%. Higher mean blood flow rates were associated with higher URR (P = 0.004) and Kt/V (P = 0.009) values. AVF stenosis was present in 12.5% and thrombosis in 3% of patients. Aneurysms were the commonest AVF complication (47%) but were not haemodynamically significant. Conclusions: Tunnelled haemodialysis catheters offered adequate blood flows and achieved adequate delivered dialysis, comparable to arteriovenous fistulae. Non-tunnelled catheters delivered poor blood flow rates and dialysis dose. Greater blood flow rates were associated with a higher delivered dialysis dose. There is a need for routine surveillance and affordable interventional procedures to prevent loss of vascular access.